UMP’s IPS and Postgraduate Association brought cheers to orphans at Hembusan Kasih Sayang Care Centre - Helmi, Mohamed Isa (2019)
Universiti Malaysia Pahang (UMP)’s Institute of Postgraduate Studies (IPS) and Postgraduate Association organised a Hari Raya Aidilfitri celebration that brought cheers to 60 children at the Hembusan Kasih Sayang Care Centre in Taman Guru here.